Menstruation impact scale development - POTUR, DİLEK (My University, 2022)
Aim: Although there are many measurement tools in the literature to measure menstruation attitudes and symptoms, there is a need for a specific measurement tool that measures the impacts of menstruation alone on women\"s life, independent of pms and dysmenorrhea. Our aim was to create a scale so that we could measure the impacts of menstruation in the study.
Materials and Methods: It is a methodological research. The sample consisted of 615 female university students. Menstrual Impact draft scale, which is developed by the researchers, subscale of Menstrual Symptom Scale (MSS) Negative impacts/ somatic complaints and introductory information form have been used as data collecting forms.
Results: After the factor analysis, a 14-item scale, consisting of physical and psychosocial impact subscales, was developed. The scale is a 5 point Likert type scale evaluated between \"5\" Strongly Agree and \"1\" Strongly Disagree. The minimum and maximum scores to be obtained from the overall scale are 14 and 70 respectively. As the score increases, the participant\"s degree of being affected by menstruation increases as well. The total explained variance of the scale is 54.92%. The Cronbach\"s alpha coefficient of the scale was 0.87.
Conclusion: The literature has been earned a valid and reliable measurement tool to specifically measure the impacts of menstruation in women\"s life. MIS (Menstrual Impact Scale) is a short, practical, and easy-to-apply scale. Its validity and reliability in different cultures should be tested.
Keywords: Hemşirelik; Kadın Hastalıkları ve Doğum Hemşireliği; Sağlık Bilimleri; Nursing; Gynecology and Obstetrics Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing